2009
DOI: 10.1007/s00296-009-0977-5
|View full text |Cite|
|
Sign up to set email alerts
|

Qualitative systemic review of randomized controlled trials on complementary and alternative medicine treatments in fibromyalgia

Abstract: The objectives of the study were identification, quality evaluation and summary of RCTs on complementary and alternative medicine as defined by the National Institute of Health with the exception of dietary and nutritional supplements. A computerized search of databases from 1990 (year of publication of the ACR criteria for fibromyalgia) to July 2007 was performed. The RCTs were assessed by a methodological quality score. A total of 23 RCTs issued from 1992 to 2007 on acupuncture, balneotherapy, thermotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 60 publications
(49 reference statements)
0
39
0
1
Order By: Relevance
“…Fibromyalgia Three medium quality systematic reviews [133-135] assessed manual therapy in patients with fibromyalgia. However, two reviews [133,134] did not include studies not already included in the UK evidence report and both concluded that there is insufficient evidence to support the effectiveness of manual therapy in the treatment of fibromyalgia.…”
Section: Resultsmentioning
confidence: 99%
“…Fibromyalgia Three medium quality systematic reviews [133-135] assessed manual therapy in patients with fibromyalgia. However, two reviews [133,134] did not include studies not already included in the UK evidence report and both concluded that there is insufficient evidence to support the effectiveness of manual therapy in the treatment of fibromyalgia.…”
Section: Resultsmentioning
confidence: 99%
“…Baranowsky et al [32] included Astin et al [27] and Sephton et al's [30] studies in a non-meta-analytic review. The two studies together suggested small but significant positive effects in reduction of pain intensity and depression.…”
Section: Resultsmentioning
confidence: 99%
“…Balneotherapy in sulfur containing hot water has been widely used for the treatment of chronic pain associated with a number of conditions including osteoarthritis and fibromyalgia [3638]. While the mechanisms responsible for the beneficial effects of balneotherapy are poorly understood, it has been reported that immersion in sulfur-rich hot water increases serum cysteine levels [39] while decreasing plasma levels of inflammatory cytokines and reactive oxygen species [40].…”
Section: Discussionmentioning
confidence: 99%